Electroencephalographic response to sodium nitrite may predict delayed cerebral ischemia after severe subarachnoid hemorrhage. - Garry, P; Rowland, M; Ezra, M; Herigstad, M; Hayen, A; Sleigh, J; Westbrook, J; Warnaby, C; Pattinson, K (Lippincott, Williams & Wilkins, 2016)
Objective Aneurysmal subarachnoid haemorrhage (SAH) often leads to death and poor clinical outcome. Injury occurring during the first 72 hours is termed early brain injury (EBI), with disruption of the nitric oxide (NO) pathway playing an important pathophysiological role in its development. Quantitative electroencephalography (qEEG) parameters such as alpha/delta frequency ratio (ADR) are surrogate markers of cerebral ischaemia. This study assessed the qEEG response to a cerebral NO donor (intravenous sodium nitrite) to explore whether this correlates with the eventual development of delayed cerebral ischaemia (DCI). Design Unblinded pilot study testing response to drug intervention. Setting Neurosciences Intensive Care Unit (NICU), John Radcliffe Hospital, Oxford, UK Patients 14 World Federation of Neurosurgeons grades 3, 4 and 5 patients (mean age 52.8; range 41-69; 11 female). Interventions IV sodium nitrite 10 mcg/kg/min for one hour. Measurements and Main Results Continuous EEG recording for two hours. The ADR was measured before and during intravenous sodium nitrite infusion. Seven out of fourteen patients developed DCI. There was a +30% to +118% (range) increase in ADR in patients who did not develop DCI (p <0.0001) but an overall decrease in ADR in those patients who did develop DCI (range +11% to -31%) (p=0.006, multivariate analysis accounting for major confounds). Conclusions Administration of sodium nitrite after severe SAH differentially influences qEEG parameters depending on the patient’s susceptibility to development of DCI. With further validation in a larger sample size, this response may be developed as a tool for risk stratification after aneurysmal SAH.